PENGARUH REBUSAN DAUN SIRSAK UNTUK MENURUNKAN NYERI GOUT ATRHITIS PADA LANSIA - Rista Apriana; Dwi Retnaingsih; Joko Supriyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background: Gout arthritis was a disease characterized by pain that occurs repeatedly caused the high levels of uric acid in the blood, The prevalence was 24.7% and the most prevalence ofhighest in Bali was 19.3%. North Sulawesi was also one of the highest prevalence 10.3%. From the preliminary data obtained from health centers Shoulders, during the year 2014, from January to March, there were 111 people diagnosed with gout arthritis. So there were about 35 people per month who had gout Arthritis. One of the non pharmacologist treatment of gout was Soursop Fruit / Soursop leaves. Methods: this research used quasi experimental, with one group pre-post test design without control. sampling of this research using total sampling technique were 35 elderly people who hadgout .Results: This study analyzes by using t-test, obtained p-value= 0.000 (p <0.05) Ho rejected and Ha accepted. Conclusion: There is an influence of soursop leaf decoction therapy for gout pain atrhitis in elderly Keywords: Soursop leaves, Gout Atrhitis Pain